Oral administration of Lentinus edodes β-glucans ameliorates DSS-induced ulcerative colitis in mice via MAPK-Elk-1 and MAPK-PPARγ pathways. Issue 11 (17th October 2016) - Shi, Limin; Lin, Qinlu; Yang, Tao; Nie, Ying; Li, Xinhua; Liu, Bo; Shen, Junjun; Liang, Ying; Tang, Yiping; Luo, Feijun
Abstract : To evaluate the anti-inflammatory effect of β-glucans from Lentinus edodes, and its molecular mechanism, the dextran sulfate sodium salt (DSS) induced colitis model of mice and the LPS-stimulated RAW264.7 cell inflammation model were used in this study. Abstract : To evaluate the anti-inflammatory effect of β-glucans from Lentinus edodes, and its molecular mechanism, the dextran sulfate sodium salt (DSS) induced colitis model of mice and the LPS-stimulated RAW264.7 cell inflammation model were used in this study. 40 ICR male mice were randomly divided into 4 groups: Control, DSS (DSS treated only), DSS + low-βGs (500 mg kg −1 d −1 ) and DSS + high-βGs (1000 mg kg −1 d −1 ). The body weight of the mice with Lentinus edodes β-glucan supplementation increased significantly compared to the DSS group and the disease activity index (DAI) was improved in both βG-treated groups. Compared with the DSS group, histopathological analysis showed that the infiltration of inflammatory cells of both βG-treated groups decreased significantly in colonic tissues. Furthermore, oral administration of β-glucans decreases the concentration of malondialdehyde (MDA) and myeloperoxidase (MPO) and inhibits the expression of iNOS and several inflammatory factors: TNF-α, IL-1β and IL-6 as well as nitric oxide (NO) of the colonic tissues. The mitogen-activated protein kinase (MAPK) pathway is closely related to the expression of pro-inflammatory factors. In the DSS-induced colitis model and the LPS-stimulated RAW264.7 cell model, βGs inhibited the expression of pro-inflammatory factors and blocked the phosphorylation of JNK/ERK1/2 and p38; βGs also suppress the phosphorylation of Elk-1 at Ser84 and the phosphorylation of PPARγ at Ser112. Altogether, these results suggest that Lentinus edodes βGs could inhibit the DSS-induced ulcerative colitis and decrease inflammatory factor expressions. The molecular mechanism may be involved in suppressing MAPK signaling and inactivation of Elk-1 and activation of PPARγ.